Motivations and perceptions for physical activity in women living with metastatic breast cancer: a qualitative interview study - Mark Liu; Sharon Kilbreath; Jasmine Yee; Jane Beith; Justin McNab; Elizabeth Dylke (BMC Cancer)
Abstract Background The beneficial role of physical activity for people living with cancer is well established. However, the importance of physical activity to women living with metastatic breast cancer is not known. As motivations and perceptions around physical activity influence behavioural uptake, a qualitative study was undertaken to explore the motivations and perceptions towards physical activity of this group. Methods Women living with metastatic breast cancer were recruited through a metropolitan cancer centre in Australia to participate in semi-structured interviews about their physical activity. Open-ended questions explored health-specific factors, goals, barriers, enablers, and interests. Interviews were recorded, transcribed and thematically analysed. Results Twenty-three women participated; median age was 60 years (IQR: 20) and median time since metastatic diagnosis was 3.3 years (IQR: 3.0). Twelve women were engaged with physical activity, seven reported intentions to be active but found it challenging, and four reported nominal interest in physical activity. Four categories, covering nine themes, were identified: (i) predispositions towards physical activity, incorporating themes on enjoyment and energy, and positivity and mental resilience; (ii) health-related motivations behind physical activity, incorporating themes on physical and mental health benefits; (iii) social motivations behind physical activity, incorporating themes on enjoying exercise with others, role models and social support, and others’ negative perceptions of metastatic breast cancer; and (iv) connections between physical activity and metastatic breast cancer, incorporating themes on prognosis uncertainty, and reframing limiting perceptions. Conclusions Participants described a wide-ranging spectrum of experiences and perceptions toward physical activity. Whilst most women perceived improved physical and mental well-being from being physically active, some women were not engaged in being physically active. Behaviour change strategies that target both their attitudes and those around them may address this gap.